2017
DOI: 10.3892/ol.2017.7722
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into metastatic processes and the therapeutic effects of gemcitabine on human pancreatic cancer using an orthotopic SUIT‑2 pancreatic cancer mouse model

Abstract: Abstract. Prognosis of pancreatic cancer is poor, thus the development of novel therapeutic drugs is necessary. During preclinical studies, appropriate models are essential for evaluating drug efficacy. The present study sought to determine the ideal pancreatic cancer mouse model for reliable preclinical testing. Such a model could accurately reflect human pancreatic cancer phenotypes and predict future clinical trial results. Systemic pathology analysis was performed in an orthotopic transplantation model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
0
19
1
Order By: Relevance
“…Hence, we used 0.3 mg/kg of gemcitabine as our treatment dose for our experimental groups. Although this dose was significantly lower than what has been used in previous small animal studies for IV administration, which range from 2 to 240 mg/kg 38,39 , we found that when this dose was given IA to mice with orthotopic pancreatic tumors there was a reduction in tumor growth when compared to the same dose administered IV. Indeed, in order to achieve the same therapeutic effect as IA administration, gemcitabine needed to be administered systemically by IV injection at over 300 times the dose thereby demonstrating the efficacy of this approach for the treatment of pancreatic cancer.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Hence, we used 0.3 mg/kg of gemcitabine as our treatment dose for our experimental groups. Although this dose was significantly lower than what has been used in previous small animal studies for IV administration, which range from 2 to 240 mg/kg 38,39 , we found that when this dose was given IA to mice with orthotopic pancreatic tumors there was a reduction in tumor growth when compared to the same dose administered IV. Indeed, in order to achieve the same therapeutic effect as IA administration, gemcitabine needed to be administered systemically by IV injection at over 300 times the dose thereby demonstrating the efficacy of this approach for the treatment of pancreatic cancer.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous studies have shown that the therapeutic concentration of gemcitabine when given systemically to small animal models is in the range of 2–240 mg/kg 38,39 . To determine a concentration of gemcitabine which would be safe to give IA directly into the pancreas, in nude mice, a dose study was performed in which 24 nude mice (n = 3 per group) were given different gemcitabine concentrations (50, 30, 15, 5, 1, 0.5, 0.3 and 0.2 mg/kg) once a week for two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…For the antitumor study using orthotopic model, NNPs/CLT treatment group showed no obvious toxicity to major organs compared to CLT solution group. Orthotopic pancreatic cancer models have been reported to develop metastasis to adjacent organs such as liver and gastrointestinal tract34., 35.. In our study, saline, CLT solution, and NPs/CLT all showed obvious liver metastases with dense nuclei clusters representing tumor cells (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…For the antitumor study using orthotopic model, NNPs/CLT treatment group showed no obvious toxicity to major organs compared to CLT solution group. Orthotopic pancreatic cancer models have been reported to develop metastasis to adjacent organs such as liver and gastrointestinal tract 34. , 35.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation